Synthesis of cis bis-beta-lactams via Staudinger cycloaddition reaction using C-2-symmetric 1,2-diamines - Shaikh, A. L.; Puranik, Vedavati G.; Deshmukh, A. R. A. S. (Tetrahedron, 2005)
An efficient stereoselective synthesis of bis-beta-lactams via cycloaddition reaction (Staudinger reaction) of ketenes with bisimines derived from C-2-symmetric 1, 2-diamines is described. The reaction provided diastereomeric mixture of meso and C-2-symmetric cis-bis-beta-lactams with higher selectivity for meso-bis-beta-lactams. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: imines; ketenes; Staudinger cyclo-addition reaction; stereoselective synthesis